Coordinated preparation and recovery of a post-disaster multi-energy distribution system considering thermal inertia and diverse uncertainties - Li, Zhengmao (2023)
Low-probability but high-impact extreme events, such as floods, earthquakes, hurricanes, etc., could threaten the security of a multi-energy system, especially on the distribution level, and cause severe energy supply outages. In this paper, a coordinated restoration method is presented for the renewable energy-integrated multi-energy distribution system (MDS) with several coupling points to coordinate the preparation and load recovery stages after the extreme event. First, the MDS restoration is comprehensively modeled with coupled power and thermal network constraints. Especially, the thermal inertia, which is in the form of pipe storage and thermal demand response of smart buildings to serve as a buffer when the source fails, is fully utilized to reduce the energy supply cost after disasters. Secondly, both preparation and load recovery stage measures are employed to facilitate efficient and reliable system restoration. Furthermore, multiple uncertainties from the renewable generation and power demands in the MDS restoration are dealt with via a risk-averse two-stage stochastic programming approach. Finally, simulation results validate the effectiveness of our method and its superiority over the traditional restoration methods.